SOFC (Solid Oxide Fuel Cell) cathode material as well as preparation method and application thereof
By doping strontium, yttrium, cobalt and iron elements into the SOFC cathode material, a material with the chemical formula (La1-x-ySrxYy)(Mn1-m-nComFen)O3 is formed, which solves the problem of high polarization impedance of SOFC cathode material, and improves battery performance, which is suitable for medium-temperature SOFC applications.
Patent Information
- Application Number
- CN202411984689.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
The working temperature of the SOFC cathode material is too high or too low, which will increase the polarization impedance of the battery, which will affect the electrochemical performance of the material.
The SOFC cathode material with the chemical formula (La1-x-ySrxYy)(Mn1-m-nComFen)O3 is used. This material can enhance the crystal structure stability of the cathode material, reduce polarization impedance, and improve the redox reaction rate and power density by doping strontium and yttrium at the A-position of LaMnO3.
It significantly reduces the polarization impedance of the battery, improves the redox reaction rate and power density, and thus improves the electrochemical performance of the battery, meeting the demand for high-performance cathode materials by medium-temperature SOFC.
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of solid oxide fuel cells, and in particular to a SOFC cathode material and a preparation method and application thereof. Background Art
[0002] Solid oxide fuel cells (SOFCs) are mainly composed of three parts, namely the anode porous electrode, the cathode porous electrode and the solid electrolyte layer. Fuels such as hydrogen are connected to the anode through pipelines, and oxidant materials such as oxygen are introduced into the cathode. The solid electrolyte layer in the middle can prevent the mixing of the anode and cathode fuels and oxidants from causing combustion, and on the other hand, it transports carriers from the cathode to the anode. After reaching the anode, oxygen ions react with hydrogen and other fuel gases to produce electrons. The external circuit can transfer the generated electrons to the cathode to supplement the discharge process.
[0003] SOFC is considered to be the most promising energy utilization device due to its many advantages. Its most significant advantages include: (1) SOFC has high power generation efficiency. In large-scale systems, the power generation efficiency can reach more than 60%, and in cogeneration systems, the comprehensive efficiency can even exceed 80%. This is because it can directly convert the chemical energy of the fuel into electrical energy, reducing the loss in the energy conversion process. For example, in some industrial application scenarios, SOFC can efficiently use fuel to generate electricity, reducing energy consumption and costs; (2) It has strong fuel adaptability and can use a variety of fuels, including hydrogen, carbon monoxide, natural gas and even some hydrocarbons. This fuel is suitable for a variety of applications. (1) The adaptability of SOFC makes it have great advantages in the case of diversified energy supply; (2) Low emissions. Since the chemical reaction process inside it is relatively clean, it produces fewer pollutants, especially nitrogen oxides and sulfur oxides, which are of great significance to environmental protection and can meet increasingly stringent environmental protection requirements; (3) High reliability. There are no moving parts, so the probability of mechanical failure during operation is low, the maintenance cost is relatively low, and the reliability and stability of the system are high; (4) Waste heat can be utilized. A large amount of waste heat is generated during operation, which can be recovered and utilized through cogeneration to further improve the comprehensive utilization efficiency of energy.
[0004] However, when SOFC is working, the cathode oxygen reduction reaction is relatively slow and requires a thermal activation process, so its operating temperature needs to be in the range of 700-1000℃. High temperature places very stringent requirements on materials. Not only does it require the use of expensive high-temperature resistant materials, but it also takes a long time during startup and shutdown, and it also brings problems such as thermal stress. However, lowering the temperature will cause the interfacial polarization resistance of the battery to increase rapidly, which in turn affects the electrochemical properties of the material. Therefore, researchers have focused their main efforts on developing medium-temperature (600-800℃) SOFC.
[0005] Therefore, there is an urgent need to provide a SOFC cathode material that can reduce the polarization impedance of the battery while improving its electrochemical performance. Summary of the invention
[0007] A technical problem to be solved by the present disclosure is that an operating temperature of a SOFC cathode material that is too high or too low will increase the polarization impedance of the battery and thus affect the electrochemical performance of the material.
[0008] In order to solve the above technical problems, the first aspect of the embodiment of the present disclosure provides a SOFC cathode material, the chemical formula of the SOFC cathode material is (La 1-x-y Sr x Y y )(Mn 1-m-n Co m Fe n )O3; wherein, 0<x≤0.5, 0<y≤0.5, 0<m≤0.5, 0<n≤0.5, m+n≤0.5.
[0009] In some embodiments, 0.2≤x+y≤0.4, 0.4≤m+n≤0.5.
[0010] In some embodiments, the polarization impedance of the SOFC cathode material at a temperature of 700° C. is no greater than 0.2 Ω·cm 2 .
[0011] In some embodiments, the power density of the SOFC cathode material at a temperature of 750°C is no greater than 1-2 W / cm 2 .
[0012] In some embodiments, the performance decay rate of the SOFC cathode material is no more than 5% when cycled for 500 hours at a temperature of 650-750°C.
[0013] A second aspect of the present disclosure provides a method for preparing a SOFC cathode material, the method comprising the following steps:
[0014] (1) mixing lanthanum salt, manganese salt, strontium salt, yttrium salt, cobalt salt and iron salt in the presence of an organic solvent and a complexing agent to obtain a sol;
[0015] (2) calcining the sol obtained in step (1);
[0016] The molar ratio of the lanthanum salt calculated as lanthanum, the strontium salt calculated as strontium, the yttrium salt calculated as yttrium, the manganese salt calculated as manganese, the cobalt salt calculated as cobalt and the iron salt calculated as iron is (1-xy):x:y:(1-mn):m:n; wherein, 0<x≤0.5, 0<y≤0.5, x+y≤0.5, 0<m≤0.5, 0<n≤0.5, m+n≤0.5.
[0017] In some embodiments, 0.2≤x+y≤0.4, 0.4≤m+n≤0.5.
[0018] In some embodiments, in step (1), the lanthanum salt is lanthanum nitrate and / or lanthanum chloride, preferably lanthanum nitrate.
[0019] In some embodiments, the manganese salt is selected from at least one of manganese nitrate, manganese chloride and manganese sulfate, and is more preferably manganese nitrate.
[0020] In some embodiments, the strontium salt is strontium nitrate and / or strontium chloride, more preferably strontium nitrate.
[0021] In some embodiments, the yttrium salt is selected from at least one of yttrium nitrate, yttrium bromide and yttrium chloride, and more preferably yttrium nitrate.
[0022] In some embodiments, the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride, cobalt bromide, cobalt carbonate and cobalt citrate, and is more preferably cobalt nitrate.
[0023] In some embodiments, the iron salt is selected from at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric bromide, and is more preferably ferric nitrate.
[0024] In some embodiments, the organic solvent is ethylene glycol and the complexing agent is citric acid.
[0025] In some embodiments, in step (1), the mixing conditions include at least: a temperature of 75-90° C. and a time of 2-4 h.
[0026] In some embodiments, in step (2), the calcination conditions include at least: a temperature of 850-950° C. and a time of 2-5 h.
[0027] In some embodiments, step (2) further comprises: drying the sol before calcining.
[0028] In some embodiments, the drying conditions include at least: 110-130° C., and a drying time of 3-5 h.
[0029] A third aspect of the embodiments of the present disclosure provides the use of the SOFC cathode material of the first aspect and / or the SOFC cathode material obtained by the preparation method of the second aspect in a solid oxide fuel cell.
[0030] A fourth aspect of the disclosed embodiments provides a solid oxidation fuel cell, which includes an electrolyte and a cathode layer, wherein the cathode layer is prepared using the SOFC cathode material of the first aspect and / or the SOFC cathode material obtained by the preparation method of the second aspect.
[0031] In some embodiments, the preparation process of the cathode layer includes: mixing the SOFC cathode material, a binder and a dispersant to obtain a slurry, coating the slurry on the surface of the electrolyte and calcining.
[0032] Through the above technical solution, the SOFC cathode material provided by the present disclosure is based on LaMnO3, strontium and yttrium are doped in the A position of LaMnO3, and cobalt and iron are doped in the B position to obtain a chemical formula of (La 1-x-y Sr x Y y )(Mn 1-m- n Co m Fe n )O3's SOFC cathode material, through the synergistic effect of specific amounts of strontium, yttrium, cobalt and iron, can enhance the crystal structure stability of the cathode material, while significantly reducing the polarization impedance of the battery, increasing the redox reaction rate and power density, thereby improving the electrochemical performance of the battery, meeting the demand for high-performance cathode materials for medium-temperature solid oxide fuel cells. DETAILED DESCRIPTION
[0033] The following embodiments of the present disclosure are further described in detail in conjunction with the examples. The detailed description of the following embodiments is used to exemplarily illustrate the principles of the present disclosure, but cannot be used to limit the scope of the present disclosure. The present disclosure can be implemented in many different forms, not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
[0034] The present disclosure provides these embodiments to make the present disclosure thorough and complete, and to fully express the scope of the present disclosure to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of the materials, the numerical expressions and the numerical values set forth in these embodiments should be interpreted as being merely exemplary, and not as limiting.
[0035] All terms used in the present disclosure have the same meanings as those understood by those of ordinary skill in the art to which the present disclosure belongs, unless otherwise specifically defined. It should also be understood that terms defined in general dictionaries, for example, should be interpreted as having meanings consistent with their meanings in the context of the relevant technology, and should not be interpreted in an idealized or extremely formal sense, unless explicitly defined as such herein.
[0036] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered part of the specification.
[0037] In a first aspect, the present disclosure provides a SOFC cathode material, wherein the chemical formula of the SOFC cathode material is (La1-x-y Sr x Y y )(Mn 1-m-n Co m Fe n )O3; wherein, 0<x≤0.5, specifically can be 0.1, 0.2, 0.3, 0.4, 0.5, or any value between the two aforementioned values; 0<y≤0.5, specifically can be 0.1, 0.2, 0.3, 0.4, 0.5, or any value between the two aforementioned values; 0<m≤0.5, specifically can be 0.1, 0.2, 0.3, 0.4, 0.5, or any value between the two aforementioned values; 0<n≤0.5, specifically can be 0.1, 0.2, 0.3, 0.4, 0.5, or any value between the two aforementioned values; m+n≤0.5, specifically can be 0.1, 0.2, 0.3, 0.4, 0.5, or any value between the two aforementioned values.
[0038] The inventors of the present disclosure unexpectedly discovered during the research process that the SOFC cathode material is based on LaMnO3, and strontium and yttrium are doped in the A position of LaMnO3, and cobalt and iron are doped in the B position to obtain a chemical formula of (La 1-x- y Sr x Y y )(Mn 1-m-n Co m Fe n )O3's SOFC cathode material, through the synergistic effect of specific amounts of strontium, yttrium, cobalt and iron, can enhance the crystal structure stability of the cathode material, while significantly reducing the polarization impedance of the battery, increasing the redox reaction rate and power density, thereby improving the electrochemical performance of the battery, meeting the demand for high-performance cathode materials for medium-temperature solid oxide fuel cells.
[0039] According to the present disclosure, strontium and yttrium are doped in the A position of LaMnO3, wherein the strontium element is Sr 2+ The addition of yttrium in the form of Y can increase the oxygen vacancy concentration, reduce the polarization impedance, and improve the electrochemical performance of the cathode. 3+ The incorporation of cobalt and iron in the B position of LaMnO3 can enhance the stability of the crystal structure of the cathode material, inhibit the performance degradation at high temperature, and extend the service life of the cathode material. The synergistic effect of cobalt and iron in the B position of LaMnO3 can improve the stability of the crystal structure, oxygen vacancy concentration and catalytic activity, thereby effectively reducing the polarization impedance and increasing the power density of the battery, so that the cathode material exhibits better electrochemical performance at medium temperature (600-800℃).
[0040] According to the present disclosure, in order to further improve the electrochemical performance while reducing the polarization impedance, in some embodiments, 0.2≤x+y≤0.4, 0.4≤m+n≤0.5.
[0041] According to the present disclosure, in some embodiments, the polarization impedance of the SOFC cathode material at a temperature of 700°C is not higher than 0.2Ω·cm 2 The SOFC cathode material having the above polarization impedance has excellent electrochemical properties and can meet the demand for high-performance cathode materials for medium-temperature (600-800°C) solid oxide fuel cells.
[0042] According to the present disclosure, in some embodiments, the power density of the SOFC cathode material at a temperature of 750°C is not higher than 1-2 W / cm 2 , specifically 1W / cm 2 , 1.5W / cm 2 , 2W / cm 2 , or any value between the above two values. The SOFC cathode material with the above power density has excellent electrochemical properties and can meet the demand for high-performance cathode materials for medium-temperature (600-800°C) solid oxide fuel cells.
[0043] According to the present disclosure, SOFC cathode materials have excellent electrochemical properties at medium temperature (600-800°C) and long service life. In some embodiments, the performance decay rate of SOFC cathode materials is no more than 5% when circulated for 500 hours at a temperature of 650-750°C. SOFC cathode materials with the above performance decay rate have excellent electrochemical properties and can meet the demand for high-performance cathode materials for medium temperature (600-800°C) solid oxide fuel cells.
[0044] Exemplarily, the performance attenuation rate is not higher than 4.5% when circulating for 500 h at an operating temperature of 650°C; the performance attenuation rate is not higher than 4.2% when circulating for 500 h at an operating temperature of 680°C; the performance attenuation rate is not higher than 4% when circulating for 500 h at an operating temperature of 700°C; the performance attenuation rate is not higher than 3.8% when circulating for 500 h at an operating temperature of 720°C; and the performance attenuation rate is not higher than 3.5% when circulating for 500 h at an operating temperature of 750°C.
[0045] According to the present disclosure, the polarization impedance of the SOFC cathode material is measured according to the operating procedures of the electrochemical workstation, and the polarization impedance data is obtained by the electrochemical impedance spectroscopy (EIS) technique, for example, using a frequency range of usually 10 6 Hz to 10 -2The AC signal between Hz is used to disturb the battery or electrode, and the impedance values at different frequencies are measured to obtain the polarization impedance. Commonly used test equipment such as Solartron, Autolab and other electrochemical workstations have corresponding test specifications and processes. When testing the power density of SOFC single cells or electrode materials, a complete test system needs to be built, including a fuel supply system, an oxidant supply system, a temperature control system, a current and voltage measurement system, etc. Parameters such as the flow rate and purity of the fuel and oxidant need to be precisely controlled and measured. The temperature control accuracy is generally required to be within ±5°C, and the current and voltage measurement accuracy must meet certain requirements, such as the voltage measurement accuracy of not less than 0.01V, and the current measurement accuracy of not less than 0.01A. ; The performance decay rate test of SOFC cathode materials generally requires a long-term stability test of SOFC, and the test cycle is usually hundreds of hours or even thousands of hours. During the test, keep the supply of fuel and oxidant stable, and the working conditions such as temperature constant.
[0046] In a second aspect, the present disclosure provides a method for preparing a SOFC cathode material, the method comprising the following steps:
[0047] (1) mixing lanthanum salt, manganese salt, strontium salt, yttrium salt, cobalt salt and iron salt in the presence of an organic solvent and a complexing agent to obtain a sol;
[0048] (2) calcining the sol obtained in step (1);
[0049] The molar ratio of the lanthanum salt calculated as lanthanum, the strontium salt calculated as strontium, the yttrium salt calculated as yttrium, the manganese salt calculated as manganese, the cobalt salt calculated as cobalt and the iron salt calculated as iron is (1-xy):x:y:(1-mn):m:n; wherein, 0<x≤0.5, 0<y≤0.5, x+y≤0.5, 0<m≤0.5, 0<n≤0.5, m+n≤0.5.
[0050] In some embodiments, 0.2≤x+y≤0.4, 0.4≤m+n≤0.5.
[0051] According to the present disclosure, the preparation method of the SOFC cathode material is simple and suitable for industrial production.
[0052] According to the present disclosure, in order to improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, in step (1), the lanthanum salt is lanthanum nitrate and / or lanthanum chloride, preferably lanthanum nitrate.
[0053] According to the present disclosure, in order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, the manganese salt is selected from at least one of manganese nitrate, manganese chloride and manganese sulfate, and more preferably manganese nitrate.
[0054] According to the present disclosure, in order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, the strontium salt is strontium nitrate and / or strontium chloride, and more preferably strontium nitrate.
[0055] According to the present disclosure, in order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, the yttrium salt is selected from at least one of yttrium nitrate, yttrium bromide and yttrium chloride, and yttrium nitrate is more preferably selected.
[0056] According to the present disclosure, in order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride, cobalt bromide, cobalt carbonate and cobalt citrate, and cobalt nitrate is more preferably selected.
[0057] According to the present disclosure, in order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, the iron salt is selected from at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric bromide, and ferric nitrate is more preferably selected.
[0058] According to the present disclosure, the organic solvent may be an organic solvent conventionally selected in the art, such as ethylene glycol, ethanol, propanol or acetone; the complexing agent may be a complexing agent conventionally selected in the art, such as citric acid, oxalic acid or malic acid. In order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, the organic solvent is ethylene glycol and the complexing agent is citric acid.
[0059] According to the present disclosure, there is no particular restriction on the amount of organic solvent used, as long as it can dissolve the raw materials for preparing the SOFC cathode material; there is no particular restriction on the amount of complexing agent used, and in some embodiments, the molar ratio of the complexing agent to the metal ion is 0.5-2:1, specifically 0.5:1, 1:1, 1.5:1, 2:1, or any value between the above two values. The metal ion refers to all metal ions in lanthanum salts, manganese sources, strontium salts, yttrium salts, cobalt salts and iron salts.
[0060] According to the present disclosure, in some embodiments, in step (1), the mixing conditions at least include: a temperature of 75-90°C, specifically 75°C, 80°C, 85°C, 90°C, or any value between the two values; a time of 2-4h, specifically 2h, 3h, 4h, or any value between the two values. In the above embodiments, the mixing effect of the raw materials of the SOFC cathode material can be improved, thereby further improving the reaction efficiency and product yield of preparing the SOFC cathode material.
[0061] According to the present disclosure, in some embodiments, in step (2), the calcination conditions at least include: a temperature of 850-950°C, specifically 850°C, 900°C, 950°C, or any value between the above two values; a time of 2-5h, specifically 2h, 3h, 4h, 5h, or any value between the above two values. In the above embodiments, volatile impurities can be removed, the strength of the SOFC cathode material can be improved, and the yield of the SOFC cathode material can be further improved.
[0062] According to the present disclosure, in order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, step (2) further includes: drying the sol before calcining.
[0063] According to the present disclosure, in order to further improve the reaction efficiency and product yield of preparing SOFC cathode materials, in some embodiments, the drying conditions include at least: 110-130°C, specifically 110°C, 120°C, 130°C, or any value between the foregoing two values; the time is 3-5h, specifically 3h, 4h, 5h, or any value between the foregoing two values.
[0064] According to some particularly preferred embodiments of the present disclosure, a method for preparing a SOFC cathode material is provided, the method comprising the following steps:
[0065] (1) in the presence of an organic solvent and a complexing agent, mixing lanthanum salt, manganese salt, strontium salt, yttrium salt, cobalt salt and iron salt at a temperature of 75-90° C. for 2-4 hours to obtain a sol;
[0066] (2) drying the sol obtained in step (1) at a temperature of 110-130° C. for 3-5 h to obtain a dry gel, and calcining the dry gel at a temperature of 850-950° C. for 2-5 h to obtain a SOFC cathode material powder;
[0067] The molar ratio of the lanthanum salt calculated as lanthanum, the strontium salt calculated as strontium, the yttrium salt calculated as yttrium, the manganese salt calculated as manganese, the cobalt salt calculated as cobalt and the iron salt calculated as iron is (1-xy):x:y:(1-mn):m:n; wherein 0<x≤0.5, 0<y≤0.5, 0.2≤x+y≤0.4, 0<m≤0.5, 0<n≤0.5, 0.4≤m+n≤0.5;
[0068] The lanthanum salt is lanthanum nitrate, the manganese salt is manganese nitrate, the strontium salt is strontium nitrate, the cobalt salt is cobalt nitrate, the iron salt is iron nitrate, the organic solvent is ethylene glycol, and the complexing agent is citric acid.
[0069] In the above preferred embodiments, the prepared SOFC cathode material can enhance the crystal structure stability of the cathode material through the synergistic effect of specific amounts of strontium, yttrium, cobalt and iron elements, while significantly reducing the polarization impedance of the battery, increasing the redox reaction rate and power density, thereby improving the electrochemical performance of the battery.
[0070] In a third aspect, embodiments of the present disclosure provide applications of the SOFC cathode material of the first aspect and / or the SOFC cathode material obtained by the preparation method of the second aspect in solid oxide fuel cells.
[0071] In a fourth aspect, an embodiment of the present disclosure provides a solid oxidation fuel cell, which includes an electrolyte and a cathode layer, and the cathode layer is prepared using the SOFC cathode material of the first aspect and / or the SOFC cathode material obtained by the preparation method of the second aspect.
[0072] According to the present disclosure, in some embodiments, the preparation process of the cathode layer includes: mixing SOFC cathode material, a binder and a dispersant to obtain a slurry, and coating the slurry on the surface of the electrolyte for calcination.
[0073] According to the present disclosure, the binder and dispersant may be conventionally selected binders and dispersants in the art, for example, the binder may be ethyl cellulose, terpineol or PTFE adhesive; the dispersant may be polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG) or ethylenediaminetetraacetic acid (EDTA). In some embodiments, the binder is ethyl cellulose and the dispersant is terpineol.
[0074] According to the present disclosure, there is no particular limitation on the usage ratio of SOFC cathode material, binder and dispersant. In some embodiments, based on the total mass of the slurry, the usage ratio of SOFC cathode material, binder and dispersant is 1:0.05-0.2:0.06-0.12.
[0075] According to the present disclosure, in some embodiments, the conditions for calcining the slurry coated on the electrolyte surface include at least: a temperature of 900-1050°C, specifically 900°C, 950°C, 1000°C, 1050°C, or any value between the foregoing two values; a time of 1.5-2.5h, specifically 1.5h, 2h, 2.5h, or any value between the foregoing two values.
[0076] The present disclosure is described in detail below in conjunction with embodiments, but the scope of the present disclosure is not limited thereby.
[0077] In the following examples and comparative examples, unless otherwise specified, the raw materials are commercially available.
[0078] Example 1
[0079] The cathode layer preparation process includes the following steps:
[0080] (1) Lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate were weighed respectively, wherein the molar ratio of lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate was 0.8:0.1:0.1:0.6:0.2:0.2, and these precursor compounds were dissolved in a solvent containing citric acid as a complexing agent, ethylene glycol, wherein the molar ratio of citric acid to metal ions was 1.5:1, and the volume of ethylene glycol was 3 times that of citric acid; the mixture was stirred at 80° C. for 3 h to form a uniform sol; the sol was dried in an oven at 120° C. for 4 h to obtain a dry gel; the dry gel was placed in a muffle furnace and calcined at 850° C. for 4 h to obtain a sol having a chemical formula (La 0.8 Sr 0.1 Y 0.1 )(Mn 0.6 Co 0.2 Fe 0.2 ) SOFC cathode material powder of O3;
[0081] (2) SOFC cathode material powder is mixed with binder ethyl cellulose and dispersant pine alcohol to prepare a slurry, wherein the mass ratios of binder ethyl cellulose and dispersant pine alcohol are 7.5% and 6%, respectively, based on the total mass of the slurry; the slurry is coated on the electrolyte surface by screen printing and sintered at 1000°C for 2h to form a dense cathode layer.
[0082] Example 2
[0083] The cathode layer preparation process includes the following steps:
[0084] (1) Lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate were weighed respectively; lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate were weighed respectively; the molar ratio of lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate was 0.6:0.2:0.2:0.6:0.2:0.2 based on lanthanum, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate based on manganese was 0.6:0.2:0.2:0.2:0.2; these precursor compounds were dissolved in a solvent ethylene glycol containing a complexing agent citric acid, wherein the molar ratio of citric acid to metal ions was 1:1, and the volume of ethylene glycol was 3 times that of citric acid; the mixture was stirred at 75°C for 3 hours to form a uniform sol; the sol was dried in an oven at 110°C for 5 hours to obtain a dry gel; the dry gel was placed in a muffle furnace and calcined at 900°C for 3 hours to obtain a chemical formula (La 0.6 Sr 0.2 Y 0.2 )(Mn 0.6 Co 0.2 Fe0.2 ) SOFC cathode material powder of O3;
[0085] (2) SOFC cathode material powder was mixed with binder ethyl cellulose and dispersant pine alcohol, with the mass ratios of binder ethyl cellulose and dispersant pine alcohol being 10% and 7%, respectively, based on the total mass of the slurry; the slurry was coated on the electrolyte surface by screen printing and sintered at 1050°C for 1.5h to form a dense cathode layer.
[0086] Example 3
[0087] The cathode layer preparation process includes the following steps:
[0088] (1) Lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate were weighed respectively, and the molar ratio of lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate was 0.6:0.3:0.1:0.5:0.3:0.2. These precursor compounds were dissolved in ethylene glycol containing a complexing agent citric acid, wherein the molar ratio of citric acid to metal ions was 1.2:1, and the volume of ethylene glycol was 5 times that of citric acid; the mixture was stirred at 85°C for 2 hours to form a uniform sol; the sol was dried in an oven at 130°C for 4 hours to obtain a dry gel; the dry gel was placed in a muffle furnace and calcined at 880°C for 3.5 hours to obtain a chemical formula (La 0.6 Sr 0.3 Y 0.1 )(Mn 0.5 Co 0.3 Fe 0.2 ) SOFC cathode material powder of O3;
[0089] (2) SOFC cathode material powder is mixed with binder ethyl cellulose and dispersant pine alcohol to prepare a slurry, wherein the mass ratios of the binder ethyl cellulose and the dispersant pine alcohol are 5% and 10%, respectively, based on the total mass of the slurry; the slurry is coated on the electrolyte surface by screen printing and sintered at 950°C for 2.5h to form a dense cathode layer.
[0090] Example 4
[0091] The cathode layer preparation process includes the following steps:
[0092] (1) Lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate were weighed respectively, and the molar ratio of lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate was 0.6:0.25:0.15:0.5:0.25:0.25. These precursor compounds were dissolved in ethylene glycol containing a complexing agent citric acid, wherein the molar ratio of citric acid to metal ions was 1.5:1, and the volume of ethylene glycol was 8 times that of citric acid. The mixture was stirred at 90°C for 2.5 hours to form a uniform sol. The sol was dried in an oven at 125°C for 4.5 hours to obtain a dry gel. The dry gel was placed in a muffle furnace and calcined at 920°C for 2.5 hours to obtain a chemical formula (La 0.6 Sr 0.25 Y 0.15 )(Mn 0.5 Co 0.25 Fe 0.25 ) SOFC cathode material powder of O3;
[0093] (2) SOFC cathode material powder is mixed with binder ethyl cellulose and dispersant pine alcohol to form a slurry, where the mass ratios of binder ethyl cellulose and dispersant pine alcohol are 15% and 8%, respectively, based on the total mass of the slurry; the slurry is coated on the electrolyte surface by screen printing and sintered at 1020°C for 1.8h to form a dense cathode layer.
[0094] Example 5
[0095] The cathode layer preparation process includes the following steps:
[0096] (1) Lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate were weighed respectively, and the molar ratio of lanthanum nitrate, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate was 0.6:0.15:0.25:0.6:0.25:0.15 based on lanthanum, strontium nitrate, yttrium nitrate, manganese nitrate, cobalt nitrate, and iron nitrate based on iron was 0.6:0.15:0.25:0.6:0.25:0.15. These precursor compounds were dissolved in a solvent containing citric acid as a complexing agent, ethylene glycol, wherein the molar ratio of citric acid to metal ions was 2:1, and the volume of ethylene glycol was 10 times that of citric acid. The mixture was stirred at 82°C for 3.5 hours to form a uniform sol. The sol was dried in an oven at 115°C for 3 hours to obtain a dry gel. The dry gel was placed in a muffle furnace and calcined at 860°C for 4.5 hours to obtain a chemical formula (La 0.6 Sr 0.15 Y 0.25 )(Mn 0.6 Co 0.25 Fe 0.15 ) SOFC cathode material powder of O3;
[0097] (2) SOFC cathode material powder is mixed with binder ethyl cellulose and dispersant pine alcohol to form a slurry, where the mass ratios of binder ethyl cellulose and dispersant pine alcohol are 12.5% and 7.5%, respectively, based on the total mass of the slurry; the slurry is coated on the electrolyte surface by screen printing and calcined at 980°C for 2.2h to form a dense cathode layer.
[0098] Example 6
[0099] A cathode layer is prepared according to the method of Example 1, except that in step (1), lanthanum nitrate is replaced by lanthanum chloride, strontium nitrate is replaced by strontium chloride, yttrium nitrate is replaced by yttrium chloride, manganese nitrate is replaced by manganese chloride, cobalt nitrate is replaced by cobalt chloride, and ferric nitrate is replaced by ferric chloride.
[0100] Example 7
[0101] A cathode layer is prepared according to the method of Example 1, except that in step (1), the molar ratio of lanthanum nitrate based on lanthanum, strontium nitrate based on strontium, yttrium nitrate based on yttrium, manganese nitrate based on manganese, cobalt nitrate based on cobalt and iron nitrate based on iron is replaced with 0.5:0.25:0.25:0.6:0.2:0.2.
[0102] Example 8
[0103] A cathode layer is prepared according to the method of Example 1, except that in step (1), the molar ratio of lanthanum nitrate based on lanthanum, strontium nitrate based on strontium, yttrium nitrate based on yttrium, manganese nitrate based on manganese, cobalt nitrate based on cobalt and iron nitrate based on iron is replaced with 0.8:0.1:0.1:0.8:0.1:0.1.
[0104] Example 9
[0105] A cathode layer is prepared according to the method of Example 1, except that in step (1), the molar ratio of lanthanum nitrate based on lanthanum, strontium nitrate based on strontium, yttrium nitrate based on yttrium, manganese nitrate based on manganese, cobalt nitrate based on cobalt and iron nitrate based on iron is replaced with 0.5:0.25:0.25:0.8:0.1:0.1.
[0106] Comparative Example
[0107] The cathode layer preparation process includes the following steps:
[0108] (1) Weigh lanthanum nitrate and manganese nitrate respectively, the molar ratio of lanthanum nitrate to manganese nitrate is 1:1, dissolve these precursor compounds in ethylene glycol containing a complexing agent citric acid, wherein the molar ratio of citric acid to metal ions is 1:1, and the volume of ethylene glycol is 3 times that of citric acid; continue stirring at 80°C for 3.5 hours to form a uniform sol; dry the sol in an oven at 120°C for 3 hours to obtain a dry gel; place the dry gel in a muffle furnace and calcine at 850°C for 4 hours to obtain LaMnO3 powder;
[0109] (2) LaMnO3 powder was mixed with a binder ethyl cellulose and a dispersant pine alcohol to prepare a slurry, wherein the mass ratios of the binder ethyl cellulose and the dispersant pine alcohol were 7.5% and 7%, respectively, based on the total mass of the slurry; the slurry was coated on the electrolyte surface by screen printing and calcined at 1000°C for 2h to form a dense cathode layer.
[0110] Test Case
[0111] The polarization resistance (ASR) of the cathode layers prepared in Examples 1 to 9 and the comparative example at a temperature of 700°C, the power density at a temperature of 750°C, and the performance attenuation rate when cycled for 500 hours at a temperature of 650-750°C were tested. The results are shown in Table 1.
[0112] Table 1
[0113] serial number <![CDATA[ASR(Ω·cm 2 )]]> <![CDATA[Power density (W / cm 2 )]]> Operating temperature(℃) Performance decay rate (%) Example 1 0.15 1.5 700 4 Example 2 0.12 1.8 750 3.5 Example 3 0.14 1.6 650 4.1 Example 4 0.13 1.6 720 3.8 Example 5 0.16 1.7 680 4.2 Example 6 0.18 1.3 750 4.5 Example 7 0.17 1.4 720 4.4 Example 8 0.19 1.2 720 4.6 Example 9 0.18 1.3 700 4.8 Comparative Example 0.30 0.8 700 10
[0114] It can be seen from the results in Table 1 that, compared with the comparative example, when the cathode layer is obtained by the preparation method provided by the present invention in Examples 1 to 9, the synergistic effect of specific amounts of strontium, yttrium, cobalt and iron elements can enhance the crystal structure stability of the cathode material, significantly reduce the polarization impedance of the battery, and increase the redox reaction rate and power density, thereby improving the electrochemical performance of the battery and meeting the demand for high-performance cathode materials for medium-temperature solid oxide fuel cells.
[0115] So far, various embodiments of the present disclosure have been described in detail. In order to avoid obscuring the concept of the present disclosure, some details known in the art are not described. Based on the above description, those skilled in the art can fully understand how to implement the technical solution disclosed here.
[0116] Although some specific embodiments of the present disclosure have been described in detail by way of examples, it should be understood by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present disclosure. It should be understood by those skilled in the art that the above embodiments may be modified or some technical features may be replaced by equivalents without departing from the scope and spirit of the present disclosure. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict.
Claims
1. A SOFC cathode material, characterized in that: The chemical formula of the SOFC cathode material is (La 1-x-y Sr x Y y )(Mn 1-m- n Co m Fe n )O3; Among them, 0<x≤0.5, 0<y≤0.5, x+y≤0.5, 0<m≤0.5, 0<n≤0.5, m+n≤0.
5.
2. The SOFC cathode material according to claim 1, characterized in that 0.2≤x+y≤0.4, 0.4≤m+n≤0.
5.
3. The SOFC cathode material according to claim 1 or 2, characterized in that: The polarization impedance of the SOFC cathode material at a temperature of 700°C is not higher than 0.2Ω·cm 2 ; Preferably, the power density of the SOFC cathode material at a temperature of 750°C is not higher than 1-2 W / cm 2 ; Preferably, the performance attenuation rate of the SOFC cathode material is no more than 5% when cycled for 500 hours at a temperature of 650-750°C.
4. A method for preparing a SOFC cathode material, characterized in that: The method comprises the following steps: (1) mixing lanthanum salt, manganese salt, strontium salt, yttrium salt, cobalt salt and iron salt in the presence of an organic solvent and a complexing agent to obtain a sol; (2) calcining the sol obtained in step (1); The molar ratio of the lanthanum salt calculated as lanthanum, the strontium salt calculated as strontium, the yttrium salt calculated as yttrium, the manganese salt calculated as manganese, the cobalt salt calculated as cobalt and the iron salt calculated as iron is (1-xy):x:y:(1-mn):m:n; wherein, 0<x≤0.5, 0<y≤0.5, x+y≤0.5, 0<m≤0.5, 0<n≤0.5, m+n≤0.
5.
5. The preparation method according to claim 4, characterized in that: 0.2≤x+y≤0.4, 0.4≤m+n≤0.
5.
6. The preparation method according to claim 4, characterized in that: In step (1), the lanthanum salt is lanthanum nitrate and / or lanthanum chloride, preferably lanthanum nitrate; Preferably, the manganese salt is selected from at least one of manganese nitrate, manganese chloride and manganese sulfate, and more preferably manganese nitrate; Preferably, the strontium salt is strontium nitrate and / or strontium chloride, more preferably strontium nitrate; Preferably, the yttrium salt is selected from at least one of yttrium nitrate, yttrium bromide and yttrium chloride, and more preferably yttrium nitrate; Preferably, the cobalt salt is selected from at least one of cobalt nitrate, cobalt chloride, cobalt bromide, cobalt carbonate and cobalt citrate, and is more preferably cobalt nitrate; Preferably, the iron salt is selected from at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric bromide, and more preferably ferric nitrate; Preferably, the organic solvent is ethylene glycol, and the complexing agent is citric acid.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (1), the mixing conditions include at least: a temperature of 75-90° C. and a time of 2-4 hours.
8. The preparation method according to any one of claims 4 to 6, characterized in that: In step (2), the calcination conditions include at least: a temperature of 850-950° C. and a time of 2-5 h; Preferably, step (2) further comprises: drying the sol before the calcination; Preferably, the drying conditions at least include: 110-130° C., and time of 3-5 h.
9. Use of the SOFC cathode material according to any one of claims 1 to 3 and / or the SOFC cathode material obtained by the preparation method according to any one of claims 4 to 8 in a solid oxide fuel cell.
10. A solid oxide fuel cell, characterized in that: The solid oxide fuel cell comprises an electrolyte and a cathode layer, wherein the cathode layer is prepared using the SOFC cathode material according to any one of claims 1 to 3 and / or the SOFC cathode material obtained by the preparation method according to any one of claims 4 to 8; Preferably, the preparation process of the cathode layer comprises: mixing the SOFC cathode material, a binder and a dispersant to obtain a slurry, and coating the slurry on the surface of the electrolyte for calcination.